The Effect of Problem-Based Learning on Biology Achievement Grade XII-1 Students at Pakusari Senior High School - Muhammad Tyo Adli; Nadya Wulansari; Yosina Gwijangge; Ika Priantari; Beny Yulianingsih (UNIVERSITAS KHAIRUN, 2026)
This reaserch has pourpose to assess the influence of the Problem-Based Learning (PBL) approach on biology achievement among XII 1 grade students at Pakusari State High School, focusing on biotechnology material. It adopted a quantitative experimental method featuring a one-group pretest-posttest design. The findings involved 36 participants. Learning outcome data were collected via pre- and post-intervention tests. Statistical analysis encompassed descriptive statistics, normality testing, and the Wilcoxon test. Results showed pretest averages increasing from 42.5 to 65.83 in the posttest. Normality assessment confirmed non-normal distribution (Sig. < 0.05), prompting use of the Wilcoxon test, which produced a significance level of 0.000 (< 0.05). As a result, the null hypothesis (H₀) was dismissed in support of the alternative (H₁), validating a statistically meaningfull enhancement in students' biology performance pre- and post-PBL implementation. Hence, the PBL model demonstrably boosts learning outcomes effectively.